Nutrient utilization, rumen fermentation characteristics and ciliate protozoa population in sheep and goats under stall feeding - SANTRA, A; KARIM, S A (The Indian Journal of Animal Sciences, 2014)
A study was conducted on stall fed sheep and goats to assess their relative nutrient utilization, rumen fermentation characteristics and ciliate protozoa count under ad lib. feeding regimen. Dry matter intake (DMI) was higher (P